Amino acid analog toxicity in primary rat neuronal and astrocyte cultures: Implications for protein misfolding and TDP-43 regulation - Dasuri, Kalavathi (2011)
Amino acid analogs promote translational errors that result in aberrant protein synthesis, and have been used to understand the effects of protein misfolding in a variety of physiological and pathological settings. TDP-43 is a protein that is linked to protein aggregation and toxicity in a variety of neurodegenerative diseases. In this study we exposed primary rat neurons and astrocyte cultures to established amino acid analogs (Canavanine and Azetidine-2-carboxylic acid), and observed both cell types undergo a dose-dependent increase in toxicity, with neurons exhibiting a greater degree of toxicity as compared to astrocytes. Neurons and astrocytes exhibited similar increases in ubiquitinated and oxidized protein following analog treatment. Analog treatment increased Heat shock protein (Hsp) levels in both neurons and astrocytes. In neurons, and to a lesser extent astrocytes, the levels of TDP-43 increased in response to analog treatment. Taken together, these data indicate that neurons exhibit preferential toxicity and alterations in TDP-43, in response to increased protein misfolding, as compared to astrocytes.